Entrepreneurship in technology for ASEAN - Mandal, Purnendu; Vong, John (Springer, 2017)
This edited book focuses on growth and entrepreneurial development in rapidly developing countries in Asia-Pacific region. The book synthesizes the scholarly papers and ideas presented at the 3rd International Conference on Managing the Asian Century, Kuala Lumpur, Malaysia in 2015. It accounts for that fact that entrepreneurs of today are focusing more on technology and that this is happening in so-called Smart Nations. Chapters in the book elaborate on huge gains in innovation in ASEAN, China and India. Gains that are essential for national growth. Some of the issues that are covered include developments in Financial-Data Analysis, Global Healthcare, Geospatial Analysis, Lean Manufacturing, Human Resource, and Big Data and Learning Analytics.
"This book synthesizes the scholarly papers and ideas presented at the 3rd International Conference on Managing the Asian Century, Kuala Lumpur, Malaysia in 2015"--Back cover.
Keywords: ASEAN -- Congresses.; ASEAN; Entrepreneurship -- Southeast Asia -- Congresses.; Technological innovations -- Economic aspects -- Southeast Asia -- Congresses.; Pacific Area.; elektronické knihy; electronic books